Capital structure determinants of hospitality sector SMEs. - Pacheco, Luís Miguel (2016)
The main objective of this paper is to study the capital structure determinants of SMEs in the hospitality sector and how this can influence their level of indebtedness. Using panel data methodology and considering a sample of 43 Portuguese hotels we study the capital structure determinants between 2004 and 2013. The paper intends to examine the indebtedness level in light of the two main theories – the Trade-off theory and the Pecking Order theory. We chose the hospitality sector because of its importance in the Portuguese economy and because this particular sector has hardly been studied. In addition to total indebtedness, we extend the literature by analyzing the differences between short-term and long-term indebtedness. The results obtained suggest that profitability, assets tangibility, firm dimension, total liquidity and risk are key factors affecting the capital structure of hospitality sector SMEs, while growth, other tax benefits and age were not deemed relevant. These results allow us to conclude that Trade-off and Pecking Order theories should not be considered in isolation to explain the capital structure of hospitality sector SMEs.